Relationship Between The Level of Mother's Nutritional Knowledge and The Diversity of Animal Protein Intake in Toddlers at Tertek Village - Gracela, Eveline; Muniroh, Lailatul (Universitas Airlangga, 2024)
The importance of nutritional intake in the growth of toddlers has become a crucial matter, especially the intake of animal protein. Animal protein contains various essential amino acids with high bioavailability that contribute to supporting the growth and development processes of toddlers. One of the factors that can influence the diversity of animal protein consumption in toddlers is the level of mother’s knowledge. This research was conducted to analyze the relationship between mother’s nutritional knowledge level and the diversity of animal protein intake in toddlers aged 24-59 months at the Integrated Health Service Post (Posyandu) in Tertek Village, Pare District, Kediri Regency. The research design was cross-sectional with a total of 99 subjects selected through proportionate stratified random sampling. The data collection was carried out through interviews using questionnaires and Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) within the last one month. This research was conducted from January to June 2023 in Tertek Village, Pare District, Kediri Regency. Based on the research results, the majority of the mother’s nutritional knowledge was categorized as low (39.4%). Meanwhile, the diversity of animal protein intake is still relatively low (60.6%). Statistical analysis results showed a significant relationship (p=0.027) with a low-level relationship (+0.260) between mother’s nutritional knowledge and the diversity of animal protein intake in toddlers aged 24-59 months at the Integrated Health Service Post (Posyandu) in Tertek Village, Pare District, Kediri Regency. This indicates that the better the mother’s nutritional knowledge, the higher the diversity of animal protein intake in toddlers.